Economic Returns on Under-Graduate Fields of Study in Canadian Universities, 1961 to 1972 - Mehmet, Ozay (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper provides comparable estimates of private rates of return on a set of21 undergraduate courses of study at Canadian Universities in 1961, 1969 and 1972, and then attempts to explain observed shifts in the college labour market using a simple multiple regression model.